2014
DOI: 10.1136/bjophthalmol-2014-305545
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of IgG4-related disease (IgG4-RD) among idiopathic orbital inflammations and benign lymphoid hyperplasias using two consensus-based diagnostic criteria for IgG4-RD

Abstract: This is the largest review of IgG4 staining among biopsy-confirmed IOI and OBLH. IgG4-ROD accounted for a substantial proportion of OBLH. The prevalence among cases of IOI was considerably reduced when the consensus diagnostic criteria were used in place of the comprehensive diagnostic criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 24 publications
4
39
1
6
Order By: Relevance
“…Exceptional tumor-like appearance can be related with pseudolymphomas. Recent data suggest that a significant part of benign lymphoid hyperplasia can be associated with IgG4-related orbital disease using the comprehensive diagnostic criteria for IgG4-related disease [10]. …”
Section: Discussionmentioning
confidence: 99%
“…Exceptional tumor-like appearance can be related with pseudolymphomas. Recent data suggest that a significant part of benign lymphoid hyperplasia can be associated with IgG4-related orbital disease using the comprehensive diagnostic criteria for IgG4-related disease [10]. …”
Section: Discussionmentioning
confidence: 99%
“…2 Several retrospective histopathology series have found IgG4-RD to account for 5% to 36% of cases originally diagnosed as IOI and 40% to 50% of cases originally diagnosed as reactive lymphoid hyperplasia, depending on which diagnostic criteria for IgG4-RD are used. 3 The need to rule out IgG4-RD in any patient presenting with bilateral dacryoadenitis significantly strengthens the rationale for biopsy. Because lacrimal gland biopsy in unilateral dacryoadenitis has been shown to yield a specific diagnosis in 34% of cases, 4 it is possible that this proportion may be even higher when biopsying cases with bilateral onset.…”
mentioning
confidence: 98%
“…2 Although the exact pathogenesis of ME after cataract surgery remains debated, several lines of evidence indicate that release of prostaglandins and other inflammatory mediators is causative. 3 Consequently, corticosteroids are employed by cataract surgeons for their broad anti-inflammatory effects. Specifically, NSAIDs inhibit cyclooxygenase enzyme and thereby the synthesis of all downstream proinflammatory prostaglandins.…”
mentioning
confidence: 99%
“…6,8 A retrospective histopathologic review of 65 biopsies performed because of orbital enlargement indicated that IgG4-related disease may account for 10.7%-27.7% of cases initially diagnosed as idiopathic orbital inflammation or orbital benign lymphoid hyperplasia, which are idiopathic conditions that cause nonneoplastic enlargement of orbital tissue. 9 Orbital IgG4-related disease is the fifth most common organ-specific manifestation, most often presenting with painless proptosis and diplopia without systemic illness. 6,9 Diagnostic criteria Organ-specific diagnostic criteria for IgG4-related disease have been published.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…9 Orbital IgG4-related disease is the fifth most common organ-specific manifestation, most often presenting with painless proptosis and diplopia without systemic illness. 6,9 Diagnostic criteria Organ-specific diagnostic criteria for IgG4-related disease have been published. 3 Diagnosis requires a compatible clinical history and histopathologic findings and the exclusion of a broad differential diagnosis, and it is supported by an elevated serum IgG4 level.…”
Section: Clinical Manifestationsmentioning
confidence: 99%